Pengaruh Strategi Bisnis terhadap Kinerja Lembaga Pendidikan Kursus pada English 1 Samarinda - Nabila Rahmah; Muhammad Zaini (MASALIQ, 2025)
Although the influence of business strategy on institutional performance has been widely examined, studies that specifically assess institutional performance using data triangulation, where data validation is conducted through interviews with teaching staff and parents of course participants as institutional performance appraisers remain limited. This study aims to analyze the influence of business strategy on the performance of Lembaga Kursus dan Pelatihan (LKP) English 1 Samarinda. A qualitative approach with a survey and case study design was employed, involving 20 participants selected through simple random sampling. Data were collected using interview instruments and analyzed using descriptive qualitative techniques through the stages of data reduction, data display, and verification. The findings indicate that the business strategy of English 1 Samarinda, developed through the integration of operational management, digital marketing, service digitalization, service standardization, and human resource competency strengthening, has a positive influence on institutional performance. These results contribute to the development of strategic management theory in nonformal educational institutions and broaden understanding of the application of business strategies to improve course institution performance in the Indonesian local context. The study concludes that integrating business strategies that encompass teaching methods, digital marketing, service standards, and human resource competency development is crucial for enhancing the performance of LKP English 1 Samarinda, and recommends that institutional managers strengthen the continuous implementation of these strategies and improve physical facilities to maintain optimal service quality. The implications of this research include theoretical contributions to enriching the strategic management literature on nonformal educational institutions and practical implications for course providers, while also opening opportunities for further exploration of the effects of business strategy in other course institution contexts.